Correlation between quality of life and gender, age, aganglionosis level, and surgical technique in pediatric patients with Hirschsprung disease post pull-through at Dr. Wahidin Sudirohusodo Hospital, Makassar - Nikma, Andi; Sulmiati,; Wirawan, Ahmad; Habar, Tommy Rubyanto; Mariana, Nita; Mantu, Farid Nur; Hamid, Firdaus; Makkadafi, Munawir; Faruk, Muhammad; Laidding, Sachraswaty Rachman (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Hirschsprung disease (HD) is a congenital disorder characterized by the absence of ganglion cells in the Auerbach and Meissner plexuses, leading to functional bowel obstruction. The pull-through procedure, including the Duhamel, Swenson, and Soave techniques, is the standard surgical treatment. However, postoperative complication remain prevalent, significantly impacting patients’ quality of life (QoL). This study aims to evaluate the impact of aganglionosis level and surgical techniques on the QoL of HD patients using the PedsQL Gastrointestinal Scale.Methods: This retrospective cohort study included 400 HD patients who underwent pull-through surgery from January 2018 to December 2022 at Wahidin Sudirohusodo Hospital, Makassar. Data were collected from medical records, and QoL was assessed using the PedsQL GI questionnaire and statistical analyses were performed Chi-square tests.Results: A total of 400 patients were analyzed. The majority were male (63.7%) and had ultra-short segment aganglionosis (52.5%). The Duhamel technique was the most commonly used (49.0%). QoL was significantly associatied with gender (p=0.023) and aganglionosis level (p=0.001), but not with age (p=0.118) of surgical technique (p=0.489). Patients with good QoL were predominantly male and had ultra-short segment aganglionosis.Conclusions: gender and aganglionosis level significantly impact QoL in HD patients post pull-through, while age and surgical technique do not. Regular QoL assessments using PedsQL GI may improve postoperative patient management.